Comparison of the EQ-5D-Y-5L, EQ-5D-Y-3L and PedsQL in children and adolescents - Janine Verstraete; Des Scott (SpringerOpen, 2022)
Abstract Background There is an increased use of Patient-Reported Outcome Measures (PROMs) in children and adolescents. The aim of this study was to compare the feasibility, concurrent validity and known-group validity of the EQ-5D-Y-3L (Y-3L), EQ-5D-Y-5L (Y-5L) and PedsQL self-report PROMs. Methods Five hundred and fifty children and adolescents, aged 8-15-years, with acute and chronic health conditions and a general population sample were recruited from schools and hospitals in Cape Town South Africa. All respondents self-completed the Y-5L, PedsQL, Self-Rated Health Question and Y-3L. Feasibility of the measures was determined by comparing the number of missing responses. Convergent validity was assessed by Spearman's and Intra-class correlations on the corresponding items and summary scores respectively. Known-groups validity across health conditions was assessed across the summary scores of the measures with analysis of variance (ANOVA). Results The Y-3L and Y-5L had a total of 1% and 3.5% missing responses compared to 19% on the PedsQL. Similar items on the PedsQL and Y-3L/Y-5L showed high correlations (> 0.5) and related items showed moderate correlations (0.3). PedsQL total score was moderately and significantly associated with Y-3L and Y-5L level sum and VAS scores. The Y-3L and Y-5L level sum and VAS scores showed significant differences between known health groups whereas the PedsQL only showed differences between those with acute and chronic illness. Conclusion The results of this study show that the Y-3L and Y-5L showed comparable psychometric validity to the PedsQL. When considering the choice between the PedsQL, Y-5L and Y-3L these study results indicate that the EQ-5D-Y instruments (Y-3L and Y-5L) are recommended for studies assessing known-group validity or where missing data should be minimised. The PedsQL generic measure may be preferable in future studies including the general population where a ceiling effect is anticipated. When considering the choice between the Y-5L and the Y-3L there was no systematic difference in the validity between these instruments or between the Y-3L or Y-5L and the PedsQL. Thus, the selection of EQ-5D-Y measures to include in future studies should be guided by the characteristics of the population to be tested.